Suburban goose management: insights from New York state - Swift, Bryan L. (DigitalCommons@University of Nebraska - Lincoln, 2000)
New York State Department of Environmental Conservation (DEC) conducted studies in suburban Rockland County, New York during 1993-2000 to help local officials develop strategies to alleviate conflicts associated with local-nesting or "resident" Canada geese {Branta canadensis). Annual counts indicated a relatively stable population of approximately 2,500-3,000 resident geese in the county, far fewer than anecdotal reports suggested. Counts tended to increase in towns where there was little or no goose management, whereas numbers declined in towns with active goose management efforts (i.e., egg-addling, capture and removal, or use of border collies). Egg-addling programs did not result in immediate reduction of goose numbers, but provided some relief at nesting sites and may have limited population growth. Removal of geese reduced total goose numbers but did not provide year-round relief at all capture locations. Use of border collies alleviated problems at many locations, but most displaced birds remained nearby. Costs of management alternatives varied widely, but all techniques were useful in a comprehensive management program. There is no quick or easy solution to goose problems in suburban areas; a coordinated community effort delivered by municipal "goose control officers" is recommended.